The Effect of Financial Literacy And Green Economy On Stock Purchase Decisions With An Understanding Of The Green Economy As A Moderating Variable In The Millennial Generation In Central Kalimantan. - Rakhmawati, Dewi; Octobery, Revnussa; Nugroho, Sanjayanto; Buji, Grace Evelina; Hidayati (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyse the effect of financial literacy and green economy on stock purchase decisions, with green economy understanding as a moderating variable, among millennials in Central Kalimantan. Using a quantitative approach with an associative design, this study involved 100 respondents who are active investors in the Central Kalimantan capital market. Data were analysed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that financial literacy and green economy have a positive and significant effect on stock purchase decisions. Understanding the green economy is proven to moderate the relationship between financial literacy and stock purchase decisions, but is not significant in moderating the relationship between the green economy and stock purchase decisions. These findings emphasise the importance of integrating financial education and the concept of a sustainable economy to improve the quality of investment decisions among millennials